Building Loyalty Of Members Of The Muhammadiyah Student Association Through Organizational Management - Agung Taufik Wahyud; Muhammad Fadil Zuhri; Fauhan Thirafi (Penerbit Hellow Pustaka, 2024)
This research aims to determine the role of IMM organizational management in building loyalty of organizational members. This research is descriptive research with a qualitative approach. Data analysis used the Miles and Hubberman model. The results obtained from this research are the role of organizational management in building loyalty of members of the IMM organization: (1) cadre management in IMM is able to build member loyalty by strengthening understanding of ideology and organizational movements so as to create cadres who are willing to serve the organization, (2) management organization and leadership form a good organization so that: a) provide clear mechanisms so that members can carry out their duties in accordance with the organization's goals, b) form an organizational environment that supports members to be loyal to the organization, c) provide space for members to take roles in the organization without considering their position, (3) forming a system of movement and action that becomes a forum for individuals to realize common goals, (4) building organizational networks and activities as social capital by: a) through implementing work programs to build social networks for organizations and individuals, b) through cadre activities to instill organizational values into members.